Shared Learning In and From Transformational Development Programs - Wilson, Paul N. (2011)
Faith-based, transformational development organizations infrequently utilize impact assessment tools as learning activities. The author argues that the real and significant barriers to program assessment can be managed if shared learning becomes a core value within the organization. By integrating Biblical teaching and program assessment activities with what it means to be a learning organization, the paper outlines a strategy for sharing valuable experiences about holistic development within and outside the faith-based development community.
Keywords: learning organization; impact assessment; Evaluation